2011
DOI: 10.4020/jhrs.27.255
|View full text |Cite
|
Sign up to set email alerts
|

Box Isolation for Atrial Fibrillation

Abstract: Since the first report of catheter ablation curing atrial fibrillation (AF), numerous techniques have evolved, from linear ablation to segmental pulmonary vein (PV) isolation, extensive encircling PV isolation, LA linear ablation, ablation of complex fragmented atrial electrograms (CFAE) and stepwise ablation. We developed a new approach for complete isolation of the posterior LA including all PVs, namely box isolation. In the posterior LA, there are many arrhythmogenic substrates for AF, including the trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…12 As an explanation for these results, several studies have suggested that the LAPW plays an important role in initiating and maintaining AF. [13][14][15][16] However, there is little evidence regarding which LSPAF patients achieve sufficiently good outcomes from PVI plus PWI alone. Therefore, the endpoint of catheter ablation of LSPAF patients has never been determined.…”
Section: Efficacy Of Pvi Plus Pwi For Lspafmentioning
confidence: 99%
“…12 As an explanation for these results, several studies have suggested that the LAPW plays an important role in initiating and maintaining AF. [13][14][15][16] However, there is little evidence regarding which LSPAF patients achieve sufficiently good outcomes from PVI plus PWI alone. Therefore, the endpoint of catheter ablation of LSPAF patients has never been determined.…”
Section: Efficacy Of Pvi Plus Pwi For Lspafmentioning
confidence: 99%
“…Therefore, we developed an approach for a complete isolation of the posterior LA including all PVs, namely the Box isolation (BOXI). 10,11 Furthermore, an individualized approach for AF ablation based on low-voltage areas (LVAs), which are correlated with atrial fibrosis, has been provided. [12][13][14][15][16] Previous studies reported that LVA ablation after PVI improved the success rate in persistent AF patients with LVAs.…”
Section: Introductionmentioning
confidence: 99%
“…There are three basic strategies for modification of AF substrate: LA defragmentation by ablation of the complex fragmented atrial electrograms (CFAE), linear ablation of LA and ganglionated plexi ablation [3,[21][22][23][24][25][26][27][28][29]. CFAE are the electrograms during AF which have short cycle length (<120ms) or which are fractionated into two or more components, or show continuous atrial electrical activation [50].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%